Kompetencje reportera na rynku pracy na podstawie analizy materiałów projektu Szkoły Społecznej Uważności - Pawlak-Hejno, Elżbieta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The aim of this article is to bring the idea of The School of Social Mindfulness closer to the scope determined by the title question. Using a qualitative analysis of the reporters’ auto-thematic statements, one can enunciate a repertoire of basic skills self-defined by professionals. The material corpus is composed of the statements collected in the volumes “Reporterzy bez fikcji” (Wojcińska 2011) and “Autoportret reportera” (Kapuściński 2003), as well as interviews given by Katarzyna Michalak, the co-creator of the workshops. The reflection on the condition of the Polish reportage and on the place of the genre in the era of the appreciation of sensationalist and entertainment-focused messages is born on the basis of the research.
Reporters competencies on the labor market based on the analysis of materials of the School of Social Mindfulness Project
Keywords: reportage; reporter’s competences; media education